The Role of Job Satisfaction in Mediating the Influence of Work Environment and Work Motivation on Employee Performance at Agung Bali Souvenirs in Badung Bali - I Gusti Ayu Inten Miranti ARIMBAWA; Ni Luh Putu INDIANI; Ida Ayu SURASMI (PT Keberlanjutan Strategis Indonesia, 2025)
Bali, as a prominent tourist destination, continues to experience growth in tourist visits, prompting the need for supporting facilities, including souvenir centers. Souvenirs play a vital role in tourism, and their high demand presents a promising business opportunity. With the increasing number of souvenir outlets, from traditional to modern, businesses must enhance their competitiveness by improving their human resources to achieve optimal performance. Therefore, this study aims to analyze factors affecting employee satisfaction and performance to support business goals. This study examines the mediating role of job satisfaction in the relationship between work environment, work motivation, and employee performance at Agung Bali Oleh-oleh, Badung, Bali. The study population includes all employees at Agung Bali Oleh-oleh in Badung. A sample of 70 respondents was selected using a questionnaire. Data analysis was conducted using Partial Least Squares (PLS) to test the hypotheses. Findings reveal that the work environment has a positive but insignificant effect on job satisfaction, while work motivation has a positive and significant impact. The work environment and work motivation both positively and significantly affect employee performance. However, job satisfaction has a positive but insignificant effect on performance and does not mediate the relationships between work environment or motivation and employee performance.